Analisis Kinerja Keuangan Pemerintah Daerah Kota Bandar Lampung Sebelum Dan Setelah Memperoleh Opini WTP - Rosmiaty Tarmizi; Khairudin KHAIRUDIN; Ayu Jayadi (Universitas Bandar Lampung (UBL), 2014)
This research aims to determine the local government’s financial performance Bandar Lampung city before and after obtaining WTP. Method opinion research using qualitative methods and quantitative methods of descriptive analysis with Paired Sample t Test different quantitative Test. Data used in this study is a local government financial reports (LKPD) 2008- 2012 Bandar Lampung city that has been audited by BPK-RI region Bandar Lampung. Conclusion result this study found that the financial performance of the city government after the Bandar Lampung city WTP’s opinion is different with before WTP’s opinion, which means the local government’s financial performance Bandar Lampung city after WTP’s opinion is better before WTP’s opinion.